Review of Brain Tumor Detection using Pattern Recognition Techniques - Moitra, D; Mandal, R (International Journal of Computer Sciences and Engineering, 2025)
Malignant Brain Tumor is one of the most lethal diseases on the Earth. Identifying such a tumor at an early stage is highly necessary in order to treat it properly. Medical imaging plays an important role to detect brain tumors. Although, MRI (Magnetic Resonance Imaging) is often considered to be the most suitable technique to diagnose such a tumor, it has its own limitations. On the other hand, PET (Positron Emission Tomography) has emerged as a more efficient technique to detect a brain tumor both in its pre and post treatment stages. The present work has been carried out with an objective to plan a strategy to identify brain tumors using Artificial Neural Network (ANN) and segmented PET images.